UHD 3D medical system of small‐ and medium‐sized monitor. Issue 12 (21st November 2018) - Tong, Lu; Zhang, Xiao; Guan, Enhui; Leng, Changlin; Chen, Shuo
Abstract: With the development of ultra‐high definition (UHD) display technology and stereoscopic 3D display technology, 3D ultra‐high monitor will help surgeons obtain the spatial hierarchy of internal tissues, identify tissue surfaces and blood vessels clearly, locate the focus precisely and reduce surgery time. Compared with normal 2D medical monitors, 3D medical monitors will lose more brightness because of the 3D application, so it is necessary to design a high‐brightness backlight system to guarantee the display stability and the accuracy of the diagnosis. This paper presents a novel processing system for 4K UHD 3D medical monitor with the architecture combined with universal SOC (system on a chip) and specialized FPGA (field programmable gate array). A hardware system is designed with high efficiency and reliable brightness stability control for small‐ and medium‐sized monitors. Furthermore, we analyze the two dimming modes of linear dimming and PWM dimming for a better application in medical monitor. Abstract : This paper presents a novel processing system for 4K UHD 3D medical monitor with the architecture combined with universal SOC and specialized FPGA. A hardware system is with high efficiency and reliable brightness stability control for small‐ and medium‐sized monitors. Furthermore, we analyze the linear dimming and PWM dimming for a better application in medical monitor.